Endoscopic Ultrasound‑guided Thrombin Injection in Angiographically Unfeasible Giant Pseudoaneurysm of Gastroduodenal Artery in a Patient of Chronic Pancreatitis: An Unusual Case - Jhajharia, Ashok; Sharma, S. S.; Nijhawan, Sandeep; Puri, Shekhar; Narayan, Kumar Shwetanshu; Singh, R. P.; Dhandhu, Bhanwar Singh; Sapra, Bharat (Journal of Digestive Endoscopy, 2017)
Pseudoaneurysm is a known complication of pancreatitis associated with significant morbidity and mortality. Computed tomography (CT) localizes the pseudoaneurysm apart from the severity of underlying pancreatitis. Digital subtraction angiography with coil embolization is recommended treatment for pseudoaneurysm to avoid bleeding and surgery. However, in cases where angiographic coil embolization fails due to technical reasons, CT/ultrasonography‑ guided thrombin injection remains a viable option as described in literature. In the present case, role of endoscopic ultrasound‑guided thrombin injection into large pseudoaneurysm that was not feasible by angiographic occlusion has been highlighted. The procedure avoided surgery and its related complication.
Keywords: Chronic pancreatitis; pseudoaneurysm; thrombin